THE DETERMINATION OF THE SIGN AND THE ENERGY SPECTRUM OF PRIMARY COSMIC RADIATION - SANDOVAL VALLARTA, MANUEL; PERUSQUIA; DEOYARZABAL (UNIVERSIDAD NACIONAL AUTONOMA DE MEXICO, INSTITUTO DE FISICA, CD. MEXICO, DF, MEX, 1948)
An experiment is reported in this paper for the measurement of the complete azimuthal effect. This experiment was performed in Mexico City (geomagnetic latitude 29°, altitude 2242 m above sea level) for constant zenith angles 20°, 40°, and 60°. A characte
PHYS REV D
Keywords: DETERMINATION, SIGN, ENERGY SPECTRUM, PRIMARY, COSMIC, RADIATION; MULTIDISCIPLINARIA; QUIMICA NUCLEAR; QUIMICA DE LA RADIACION